Foreword to the Special Section on 3D Object Retrieval (3DOR2018). (April 2019) - Telea, Alexandru; Theoharis, Theoharis
Highlights: High-dimensional descriptors. Machine-learned descriptors. Texture retrieval. Graphical abstract: Image, graphical abstract